Motivasi Pengawas Sekolah dalam Peningkatan Kualitas Pendidikan di Kabupaten Aceh Tamiang - Sutiyah (JoIEM (Journal of Islamic Education Management), 2021)
One of the important pillars in the world of education in Aceh Tamiang Regency is the presence of school supervisors. The number of supervisors for junior high schools in Aceh Tamiang District is relatively limited. The purpose of the study was to analyze the motivation of school supervisors in improving the quality of teachers in Aceh Tamiang District. This qualitative research uses interview, observation, and document techniques. The results of the study indicated that the motivation of school supervisors in improving the quality of education in Aceh Tamiang Regency is very much needed. Their motivation in improving the quality of education in Aceh Tamiang District is a way to achieve eight national education standards. The number of school supervisors for the junior high school level is still very limited when compared to the number of schools. Accordingly, this is the case in Aceh Tamiang District. The existence of school supervisors is important to motivate educators and education staff in the education unit to improve the quality of their work. The quality of education in schools is the responsibility of a supervisor. To solve this problem, a policy should be taken by the local government through the Education and Culture Office of Aceh Tamiang Regency to increase the number of school supervisors for the junior high school level.